(untitled) (Research, Society and Development, 2021)
Antimicrobials are drugs that act by inhibiting the growth or death of microorganisms, being the second most prescribed medication class in hospitals and responsible for 20 to 50% of hospital expenses with medications. This study aimed to analyze the profile of prescriptions for restricted-use antimicrobials in an Intensive Care Unit. This is a descriptive pharmacoepidemiological study with a cross-sectional design, with a quantitative approach of statistical analysis of secondary data from the Pharmacy sector at the Hospital Universitário de Lagarto / SE (HUL), between the months of January to December 2019, approved by the Ethics and Research of the institution Institut Faculdade AGES (Opinion number: 3,758,862). Of the 329 requests for antimicrobials for restricted use for the year 2019, 41.51% of them were elderly patients, 52.83% were male, 26.75% were diagnosed with sepsis and 23.40% were with respiratory tract problems. The use of Carbapenemic Meropenem (35.56%), glycopeptides Vancomycin (20.67%) and Piperacillin + Tazobactam (19.77%) were the most prescribed drugs. This result can be explained by the fact that they are broad-spectrum antimicrobials, initially used as empirical therapy in situations considered serious, and later maintained as a means of having more security and a wide effectiveness against various microorganisms. Subsidizing epidemiological indicators that can be used to improve health care, can provide the efficacy of proposed treatments, in addition to guiding points that need adjustment in the flow of prescription and release of such drugs.